Pain Management Essential Topics for Examinations - Gupta, Rajesh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Pain management is a vast subject and is changing rapidly. Finding a good resource for learning, however, is difficult. Most of the available books are lengthy volumes including many details irrelevant to physicians sitting for examinations or assessment. Furthermore, books aimed at assisting preparation for entire anaesthesia exams typically address pain management in only one chapter or a few pages.   This book covers the entire curriculum relating to pain management and will make it easy to learn all aspects of the subject by covering key concepts in a reader-friendly manner. It comprises nine concise and simple chapters that aim to impart the maximum information within a limited space. These chapters address anatomy, assessment of pain, diagnosis of pain, pharmacology, non-pharmacological pain management, acute and chronic pain management, pain management in special groups, and special techniques. Pain Management: Essential Topics for Examinations will be an ideal resource for those who plan to sit for examinations, wherever they are based in the world. In addition, it will be an invaluable reference for higher and advanced pain trainees, residents, and physicians working in chronic pain.
Anatomy: Anatomy of pain pathway -- Mechanisms of pain (peripheral and central sensitisation) -- Classification of pain - nociceptive, neuropathic pain -- Acute and chronic pain -- Nociceptors. Assessment of pain: Patient evaluation – history and physical examination -- Assessment and measurement of acute pain -- Assessment of chronic pain -- Assessment in elderly -- Assessment in paediatrics. Diagnosis of pain: Radiography -- Fluoroscopy -- Ultrasonography -- Nuclear medicine and PET -- CT -- MRI -- Electromyography -- Quantitative sensory testing. Pharmacology: Opioids -- Nonopioids – NSAIDs, antidepressants, anticonvulsants, sodium and calcium channel antagonists, tramadol -- Topical agents -- Alternative and herbal pharmaceuticals -- Placebo. Non pharmacological pain management: Psychological and psychosocial evaluation -- Biofeedback -- Cognitive behavioural therapy -- Functional restoration of patients with pain -- Occupational therapy -- Hypnosis -- Relaxation and imagery -- Family support -- Pain management program. Acute pain management: Post surgical pain management -- Pain management for trauma -- Labour pain management -- Burn pain -- Acute low back pain -- Patient controlled analgesia. Chronic pain management: Neuropathic pain -- Ischaemic and visceral pain -- Fibromyalgia, arthritic and myofascial pain -- Headache -- Cancer pain -- Abdominal pain -- Neck pain and whiplash injury -- Facial pain -- Neck and arm pain -- Herpes zoster and post herpetic neuralgia -- Pain following spinal cord injury -- Chronic Low back pain -- Orofacial pain -- Trigeminal pain -- Aids related pain -- Arthritis -- CRPS -- Fibromyalgia -- Peripheral neuropathy -- Sickle cell -- phantom pain -- HIV -- Pelvic pain Special groups: Paediatric -- Addiction -- Elderly Special techniques: Acupuncture -- Intrathecal drug delivery -- Botulinum toxin -- Spinal cord stimulation -- Epidural steroids -- Facet joint injections -- Radiofrequency ablation -- Peripheral nerve stimulation -- TENS -- Physiotherapy.
Keywords: Pain medicine; Anesthesiology; Radiology; Pain Medicine; Anesthesiology; Diagnostic Radiology